Antibodies against citrullinated proteins of IgA isotype are associated with progression to rheumatoid arthritis in individuals at-risk. Issue 1 (30th January 2023) - Sokolova, Maria V; Hartmann, Fabian; Sieghart, Daniela; Bang, Holger; Steiner, Guenter; Kleyer, Arnd; Schett, Georg; Steffen, Ulrike
Abstract : Objective: Events triggering disease outbreak in individuals at-risk for rheumatoid arthritis (RA at-risk) remain unclear, and the role of the various anticitrullinated protein antibody (ACPA) isotypes in this process is still to be established. We aimed to investigate the prevalence of IgA ACPA in RA at-risk individuals, their role in the transition from the RA at-risk status to RA and their dynamics during this transition. Methods: Cross-sectional measurement of serum IgA1 and IgA2 ACPA levels was conducted in healthy controls, RA at-risk individuals and patients with RA and compared with the frequency of RA development in at risk individuals during a follow-up of 14 months. In addition, longitudinal measurements of serum IgA1 and IgA2 ACPA levels prior to, at and after the onset of RA were performed. Results: Approximately two-thirds of RA at-risk individuals were positive for serum IgA1 and IgA2 ACPA in levels comparable to IgG ACPA positive patients with RA. IgA1, but not IgA2 ACPA positivity was associated with the transition from the RA at-risk state to RA within the following 14 months. Interestingly, during this transition process, IgA1 ACPA levels declined at RA onset and also thereafter during the early phase of RA. This decline was confirmed in a second, independent cohort. Conclusion: Both IgA1 and IgA2 ACPA are present in RA at-risk individuals, but only IgA1 ACPA are associated with the progression to RA. The observed decline in serum IgA1 ACPA levels before the onset of RA might indicate starting barrier leakiness prior to disease outbreak.